The effect of reverse intergenerational support on the happiness of Chinese older adults: A moderating effect analysis based on role conflict - Zhang, Hongfeng; Li, Shunyi; Dai, Wenwen; Wang, Hanning (Frontiers in Psychology, 2023)
Intergenerational support is bidirectional. Reverse intergenerational support refers to parents providing economic, time, and spiritual support to their offspring. The emergence of reverse intergenerational support has brought about some role conflicts in different age groups. Given this, based on the survey data of 3170 elderly people from 8 sample provinces in China, this paper uses the ordered Logit model to empirically investigate the relationship between reverse intergenerational support and the happiness of the elderly in contemporary China, and the moderating effect of role conflict in the mechanism. Results show that reverse economic support will reduce the happiness of the elderly, and reverse time support and reverse spiritual support will have a significant effect on the happiness of the elderly. Furthermore, in the presence of role conflict, the effects of reverse time support and reverse spiritual support on the improvement of elderly happiness are suppressed; in the presence of role enhancement, the effect of reverse economic support on the reduction of elderly happiness is resolved. Based on the above findings, this study provides new empirical evidence for understanding the relationship between reverse intergenerational support and elderly happiness prevalent in contemporary China and provides new guidance for improving the happiness of the elderly.